Implementasi Manajemen Konseling Kesehatan Mental bagi Mahasiswa Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat: The Implementation of Mental Health Counseling Management for Undergraduate Students at Institut Teknologi and Kesehatan Muhammadiyah Kalimantan Barat - Ariani, Desti Dwi; Nugroho, Prasetyo Aji; Ghifari, Aufa; Amelia, Fitri Chalista; Assari, Faisal; Amalia, Ridha; Ulandari, Anggi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Undergraduate students are individuals who experience a transition period that focuses on searching for self-identity. During this transition period, students will experience changes in their behavior, emotions and cognition. This change will affect the mental health status of students. Mental health problems in students are a serious problem to be handled because students' mental health problems are invisible but can have bad consequences if not treated immediately. Negative stigma towards mental health has an impact on students' awareness and initiative to resolve their mental health problems. Students feel embarrassed and think that this mental health problem can heal by itself. In fact, mental health problems will get worse if they are not handled well. The importance of mental health counseling services for students as a medium for early detection of mental health problems. Mental health screening can detect several mental health problems so that existing problems can be prevented and students' mental health status can improve. The role of the academic community is very important to support the existence of mental health counseling services. Moreover, policies and service standards do not yet exist at ITEKES Muhammadiyah West Kalimantan. Thus, this underlies strategic planning activities for mental health services that can be beneficial for students and have an impact on student welfare in maintaining their mental status.